Plagiarism-Requiring a Holistic Approach - Dr. Nadeem Ikram, Dr. Nadeem Ikram (Journal of Rawalpindi Medical College, 2018)
Plagiarism is the concept of checking intruding matter from other workers’ research or writing. It refers to use of another’s information, language, or writing , when done without proper acknowledgment of the original source . Plagiarism in text documents happens in several forms, i.e., plagiarized text may be copied as such, passages may be modified or they may be translated. Plagiarism has been around for as long as humans have produced work of art and research. Easy access to web, large data bases and telecommunication has made it a reality more obvious than ever. Key factors leading to plagiarism are unawareness of citing ethics, inadequate writing skills and pressing deadlines to get published. Plagiarism can be managed by its prevention detection by plagiarism detection soft wares, and educating researchers about ethical writing. Plagiarism can not be dealt with as a simple black and white issue, the prevention of which can be achieved via threats, warnings and admonitions. The notion of ownership of text and learning is becoming complex, day by day .It needs to be understood in terms of complex relationships between text, memory, and learning borrowing.